Implementasi Corporate Social Responsibility PT. Pertamina (Persero) pada Program Siswa Mengenal Nusantara - Afifah Izzaturrahmi Ibrahim; Lukiati Komala Erdiyana; Aat Ruchiat Nugraha (LONTAR: Jurnal Ilmu Komunikasi, 2021)
ABSTRACT The diversity of tribes, religions, races, and between groups for the Indonesian people is a strength to build a great nation. The younger generation's understanding of the cultural diversity of Indonesia is fading due to the impact of globalization, so an education program for love of the homeland is needed. One of the educational programs is the Student Know the Archipelago Program which is sponsored by a company that is part of a State-Owned Enterprise (BUMN) conducted by PT. Pertamina in Papua Province. The purpose of this research is to know about implementing Corporate Social Responsibility through the student program to know Nusantara by PT Pertamina (Persero). The research method used is a descriptive study with qualitative data types through data collection techniques conducted utilizing interviews, observations, and literature studies. The results showed that in the planning phase of PT Pertamina SMN CSR program which refers to the concept of Hohnen shows there is still some inconformity implementation of CSR program due to the condition of Papua area that has limitations in access to information and communication. This limitation can make the lack of a valid CSR program SMN 2018 held by PT. Pertamina (Persero) in campaigning for the diversity of Indonesian culture. Simpulan showed that PT. Pertamina has been striving to be able to realize the CSR program as a manifestation of the responsibility of BUMN present for the state.